2016
DOI: 10.1016/j.aogh.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Cytokines and IgE in Helminth-Infected Nigerian Pregnant Women and Children

Abstract: It could be concluded that altered cytokines expression in children and pregnant women with helminth infection might have some implications on need for deworming programs to improve pregnancy outcomes and vaccine responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
3
15
0
1
Order By: Relevance
“…In our study, statistically significant higher IL-10 values were found in children with ascariasis, although they did not correlate with infection intensity of this parasite. Similar findings have been frequently reported by other researchers [66, 69, 7274], with some exceptions [47]. We also found a negative correlation between children's age and IL-10 levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, statistically significant higher IL-10 values were found in children with ascariasis, although they did not correlate with infection intensity of this parasite. Similar findings have been frequently reported by other researchers [66, 69, 7274], with some exceptions [47]. We also found a negative correlation between children's age and IL-10 levels.…”
Section: Discussionsupporting
confidence: 92%
“…Such findings are consistent with observations in studies conducted in Nigeria [47, 48], Ecuador [49], Venezuela [50], Spain [26], and Brazil [41, 51, 52]. Helminth-induced IgE is mostly characterized by a nonspecific polyclonal stimulation with only a small fraction of parasite-specific IgE.…”
Section: Discussionsupporting
confidence: 91%
“…The values of IgE in PA patients with ascariasis and giardiasis were 2.6 and 6.4 times as high as in control individuals, respectively. It should be emphasised that elevated IgE levels were found in PA patients with parasites as well as in patients free of parasites.Elevated IgE responses are well documented in classical allergies to exogenous substances, such as toxins, irritants and xenobiotics [24][25][26][27][28][29][30][31]. Apparently, a high IgE level in PA patients could be connected to their expressed sensitisation to a number of allergens, including parasites.…”
mentioning
confidence: 99%
“…IL-10 downregulates the functions of immune cells that release pro-in ammatory cytokines, both preventing the elimination of worms and protecting the host against helminth infection-related symptoms. IL-6 is also described in the literature to increase signi cantly among populations infected with helminths [12]. However, the level of TNF-α is reported not to vary [12].…”
Section: Introductionmentioning
confidence: 93%